Reforming the EU's common agricultural policy: Health check, budget review, Doha Round - Valentin Zahrnt (European Centre for International Political Economy (ECIPE), 2008)
This Policy Brief provides recommendations for agricultural policy reform in the EU. It argues, first, that all measures that distort market prices and production should be abolished. This includes production quotas, land set-asides, storage aids, export refunds, output payments, and area payments. Second, the Single Farm Payment (SFP), which provides income support to farmers independently of their current production decisions, should be phased out because it does not serve any societal need. Third, targeted subsidies that reward farmers for providing socially valued services that are not remunerated on the market, such as maintaining scenic landscapes, should be adapted. Many of these subsidies should be provided at the national or local level without or with little EU co-financing.
Keywords: 330; EU-Agrarpolitik; Agrarreform; Agrarsubvention; EU-Staaten